MANAJEMEN MUTU ISO 9001:2008 SMK NU 01 KABUPATEN KENDAL - Sukhamdan Sukhamdan; Sunandar Sunandar; Yovitha Yuliejantiningsih (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2016)
The problem in this study were how the planning, organization, implementation and control Quality Management ISO 9001:2008 is in SMK NU 01 Kendal. The purpose of this study were to describe the process of planning, organizing, implementation and process of controlling Quality Management ISO 9001: 2008 at SMK NU 01 KendalThe data collecting technic is by using documents, interviews and observation. Analysis of the data using the model of Miles and Hubberman in the following ways; (1) data collection, (2) data reduction, (3) the presentation of the data, (4) conclusion.The results of this study include, 1. Planning includes (a) the planning process step by step implementation approach that includes (1) the establishment of Total quality steering committee, (2) the process of composing a quality vision, ( b) the process of planning the formation of composing the team and (c) the process of planning the training. 2. The process of organizing include (a) the process of identity, (b) the process of break work down, (c) the process of dividing group task to each position, (d) the supervision process, (e) the coordination process. 3. The process of implementation starts with (a) process intensification team, (b) the implementation of the PDCA cycle, (c) the process of collecting feedback, (d) the process of changing the infrastructure, 4. The Process of control is (a) measure the perfomance (b) compare the performance match the standard, (c) take corrective action